Effect of body position on energy expenditure of preterm infants as determined by simultaneous direct and indirect calorimetry - Bell, Edward F. (Am J Perinatol, 2016)
Indirect calorimetry is the standard method for estimating energy expenditure in clinical research. Few studies have evaluated indirect calorimetry in infants by comparing it with simultaneous direct calorimetry. Our purpose was (1) to compare the energy expenditure of preterm infants determined by these two methods, direct calorimetry and indirect calorimetry; and (2) to examine the effect of body position, supine or prone, on energy expenditure. We measured energy expenditure by simultaneous direct (heat loss by gradient-layer calorimeter corrected for heat storage) and indirect calorimetry (whole-body oxygen consumption and carbon dioxide production) in 15 growing preterm infants during two consecutive interfeeding intervals, once in the supine position and once prone. The mean energy expenditure for all measurements in both positions did not differ significantly by method used: 2.82 (SD 0.42) kcal·kg(−1)·h(−1) by direct calorimetry and 2.78 (SD 0.48) kcal·kg(−1)·h(−1) by indirect calorimetry. The energy expenditure was significantly lower, by 10%, in the prone than in the supine position, whether examined by direct calorimetry (2.67 vs 2.97 kcal·kg(−1)·h(−1), P<0.001) or indirect calorimetry (2.64 vs 2.92 kcal·kg(−1)·h(−1), P=0.017). Direct calorimetry and indirect calorimetry gave similar estimates of energy expenditure. Energy expenditure was 10% lower in the prone position than in the supine position.